An ethnographic investigation of the implementation of the bilingual-bicultural approach for educating deaf learners focusing on South African sign language teaching at FET level - Tunzelana, Nomava Mercy (Rhodes University, Faculty of Humanities, Department of Linguistics and Applied Languages Studies)
This half-thesis reports on an ethnographic investigation of the implementation of the Bilingual-Bicultural Approach for educating Deaf learners, focusing on South African Sign Language (SASL) teaching at the Further Education and Training (FET) level in a South African School for the Deaf in the Eastern Cape. The investigation occurs within the context of the introduction, in 2015, of the SASL Curriculum and Assessment Policy Statement (CAPS) by the Department of Basic Education (DBE). The SASL CAPS introduces an approach to teaching the Deaf known as the Bilingual-Bicultural Approach. This is an approach in which natural sign language (such as SASL) is taught first and used to learn a spoken language such as English for reading and writing. Previous research on a contrastive analysis of South African English and SASL reveals that SASL is a Topic-Comment language. It is sometimes Object-Subject-Verb (OSV) or Subject-Object-Verb (SOV) while the word order of South African English is Subject-Verb-Object (SVO). Semi-structured interviews of hearing and Deaf participants reveal serious tensions between the staff and the hearing staff because Deaf culture is not adhered to by some of the hearing staff. These tensions have a negative impact on the culture of learning and teaching at the school. Observations of four lessons at an FET class taught by an SASL FET teacher show that in her teaching, SASL syntax is used in keeping with the principles of the Bilingual-Bicultural Approach. However, her signing is accompanied by unvoiced spoken language due to the influence of a previously used approach called Total Communication (TC). One of the learners, Lulu, who contributes considerably more often than other learners in the lesson, also shows the same influence of TC. Other learners are either withdrawn or copy signs from Lulu. The study concludes with the recommendation that SASL be used for initiating newcomers to school as opposed to Signed English because research in bilingualism suggests that second language learners need one natural language established first before attempting to learn a second language. Teachers are recommended to immerse themselves into Deaf culture to acquire fluency. Comments from some participants suggest that teachers require vigorous training in the Bilingual-Bicultural Approach on a continuous basis.
Keywords: South African Sign Language-- Study and teaching (Higher); Sign language acquisition -- South Africa; Education, Bilingual -- South Africa; Biculturalism -- South Africa; Ethnology -- South Africa; Culturally relevant pedagogy -- South Africa; Deaf students -- South Africa; South Africa. Department of Basic Education; Curriculum-based assessment -- South Africa; South African Curriculum Assessment and Policy Statement (CAPS)